THE PRINCIPLE OF NATIONAL SOVEREIGNTY THROUGH THE LENS OF SAINT ANDREW’S DAY NATIONAL ASSEMBLY - Mitić, Sara (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
The paper under the mentioned title, first of all, gives a historical overview of assemblies in Serbia. Then, an insight into the situation ahead of the St. Andrew's Assembly is provided. The dissatisfactions of all factors in the country, the urban and rural population, certain authorities, as well as the leading political forces are explained in detail. The circumstances that accelerated the convening of the assembly are discussed below. The reasons that contributed to the formation of the final decision on convening the Assembly can be seen through the letters, which some actors sent to others. The main part of the work is the meeting of the St. Andrew's Assembly itself. First, appeals and representations of viewpoints are presented, and then the adoption of the Law on the National Assembly of October 28, 1858. The outcomes of the St. Andrew's Assembly were also discussed: the overthrow of Prince Aleksandar Karađorđević, the return of Miloš Obrenović and the de facto disempowerment of the council, as well as the most important one - the strengthening of awareness of national sovereignty.
Keywords: principle of national sovereignty; Saint Andrew’s Day National Assembly (1858); Law on the National Assembly (1858)